Corn Starch Concentration and Thickener Type in Edible Film: Konsentrasi Tepung Jagung dan Jenis Pengental dalam Film Makanan - Vandha Nita; Lukman Hudi (Academia Open, 2025)
General Background: Edible films are biodegradable packaging materials that serve as protective barriers against moisture, gases, and solutes while maintaining food quality and safety. Specific Background: Corn starch (Zea mays L.) is a hydrophilic biopolymer capable of forming films, and its combination with hydrocolloid thickeners such as pectin, carboxy methyl cellulose (CMC), and carrageenan may alter physical, chemical, and sensory characteristics. Knowledge Gap: Limited empirical data exist regarding the combined role of corn starch concentration and thickener type in determining comprehensive edible film properties. Aims: This study aimed to determine how varying corn starch concentrations  and thickener types influence edible film characteristics using a factorial randomized complete block design. Results: The optimal formulation consisted of 2% corn starch with CMC, yielding solubility of 6.99%, thickness of 0.20 mm, texture of 50.66 N, lightness of 79.64, redness  of 1.43, yellowness  of 0.68, reducing sugar of 1.98%, moisture content of 14.54%, and neutral-to-like sensory scores for aroma, color, texture, and flavor.Novelty: The study provides a comparative evaluation of multiple hydrocolloid thickeners combined with graded corn starch levels  Implications: These findings support the selection of suitable starch–hydrocolloid formulations for developing biodegradable edible packaging with acceptable functional and sensory qualities. Highlights: The formulation using 2% starch with CMC produced the most favorable overall quality metrics. Moisture content, reducing sugar, and selected color attributes differed significantly across treatments. Sensory evaluation indicated neutral-to-positive acceptance for aroma, color, texture, and flavor. Keywords:Edible Film; Corn Starch; Hydrocolloid Thickener; Biodegradable Packaging; Physicochemical Properties